Risk factors of recurrent secondary hyperparathyroidism after adequate primary surgical treatment - Kuo, Yu-Chi; Wang, Shang-Yu; Hung, Yu-Liang; Hsu, Chih-Chieh; Kou, Hao-Wei; Chen, Ming-Yang; Tsai, Chun-Yi; Chang, Chih-Hsiang; Wang, Yu-Chao; Hsu, Jun-Te; Yeh, Ta-Sen; Lee, Wei-Chen; et al. (Frontiers in Endocrinology, 2023)
Background Secondary hyperparathyroidism (SHPT) is a common condition in patients with end-stage renal disease (ESRD) who are on dialysis. Parathyroidectomy is a treatment for patients when medical therapy has failed. Recurrence may occur and is indicated for further surgery in the era of improved quality of care for ESRD patients. Methods We identified 1060 patients undergoing parathyroidectomy from January 2011 to June 2020. After excluding patients without regular check-up at our institute, primary hyperparathyroidism, or malignancy, 504 patients were enrolled. Sixty-two patients (12.3%, 62/504) were then excluded due to persistent SHPT even after the first parathyroidectomy. We aimed to identify risk factors for recurrent SHPT after the first surgery. Results During the study period, 20% of patients who underwent parathyroidectomy at our institute (in 2019) was due to recurrence after a previous parathyroidectomy. There were 442 patients eligible for analysis of recurrence after excluding patients with the persistent disease (n = 62). While 44 patients (9.95%) had recurrence, 398 patients did not. Significant risk factors for recurrent SHPT within 5 years after the first parathyroidectomy, including dialysis start time to first operation time < 3 years (p = 0.046), postoperative PTH >106.5 pg/mL (p < 0.001), and postoperative phosphorus> 5.9 mg/dL (p = 0.016), were identified by multivariate analysis. Conclusions The starting time of dialysis to first operation time < 3 years in the patients with dialysis, postoperative PTH> 106.5 pg/mL, and postoperative phosphorus> 5.9 mg/dL tended to have a higher risk for recurrent SHPT within 5 years after primary treatment.